An Analysis of Students’ Narrative Text Translation from English to Indonesian at the Tenth Grade Students of SMA N 3 Kota Jambi Academic Year 2018/2019 - Laela Fitriyani; Wennyta Wennyta (Universitas Batanghari Jambi, 2019)
This research was done to analyze the translation methods used by the tenth of social grade students at SMA N 3 Kota Jambi Academic Year 2018/2019. The method of this research was descriptive qualitative. The sample of this research was the tenth of social grade students at SMA N 3 Kota Jambi. Then to get the sample of this research, the researcher used random sampling technique. The instrument of this research was a translation test. In translation analysis processes, the researcher used theory of translation method based on Newmark Theory. The findings of this research showed that there are only four methods used by the students in translating the text. They are Word-For-Word Translation, Literal Translation, Free Translation, and Communicative Translation. It can be seen from the table that the most dominant method used by the 26 students was literal translation method. The second dominant was word-for-word translation method. Meanwhile, the third and fourth translation method applied by the students was free translation and communicative translation. Then, there are four methods which did not applied by the students in translating the story. They were faithful translation, semantic translation, adaptation translation, and idiomatic translation method. Here, the students used more than one method to translate the narrative text. Based on the data, literal translation method is the most dominant method used by the students. It happens because the students just translate the words by its literal meaning and they tried to achieve the nearest equivalence meaning in the target language.Keywords: Analysis, Translation Methods, Narrative Text.